On the origin of plasma sheet reconfiguration during the substorm growth phase. Issue 17 (9th September 2017) - Gordeev, Evgeny; Sergeev, Victor; Merkin, Viacheslav; Kuznetsova, Maria
Abstract: Recently, Hsieh and Otto (2014) suggested that transport of the closed magnetic flux to the dayside reconnection region may be a key process which controls the reconfiguration of magnetotail during the substorm growth phase. We investigate this problem using global self‐consistent MHD simulations and confirm that magnetotail reconfiguration is essentially a 3‐D process which cannot be fully described based on 2‐D‐like tail evolution powered by the magnetic flux loading into the lobes. We found that near‐Earth return convection strength on the nightside is directly related to the intensity of dayside reconnection, which causes the formation of antisunward azimuthal pressure gradients that force plasma to flow toward the dayside magnetopause. This near‐Earth part of global convection develops immediately after the onset of dayside reconnection and reaches a quasi‐steady level in 10–15 min. Its magnitude exceeds the total sunward flux transport in the midtail plasma sheet at X ≈−20 R E by an order of magnitude, causing significant amount (0.1–0.2 GWb) of closed magnetic flux to be removed from the near‐Earth plasma sheet during moderate substorm. In that region the B z depletion and current sheet thinning are closely related to each other, and the local J y ( B z ) relationship in the simulations matches reasonably well the power law expression found in the plasma sheet. In summary, global simulations confirm quantitatively that near‐Earth return convection is primarily responsible for the severe depletion of the closed magnetic flux in the plasma sheet, major tail stretching, and current sheet thinning in the near magnetotail at r < 15 R E . Key Points: Global MHD (LFM) simulations of magnetotail growth phase dynamics following north‐south IMF turnings Return convection at r < 10 R E on the nightside is proportional to E KL and by an order of magnitude higher than in the midtail at X =− 20 R E Removal of closed magnetic flux by return convection controls the major reconfiguration of near magnetotail during substorm growth phase